2021
DOI: 10.1182/hematology.2021000319
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Minireview: Should warfarin or a direct oral anticoagulant be used in patients presenting with thrombosis in the splanchnic or cerebral veins?

Abstract: Case 1: A 23-year-old female third-year medical student who has no medical history seeks treatment for abdominal distention. She takes an estrogen-containing birth control pill and does not smoke or consume alcohol. Family history is unremarkable. Physical examination is significant for abdominal distention, and an abdominal fluid wave is detected. Complete blood count is normal. Imaging confirms occlusive thrombosis of the main portal vein. On endoscopy, grade 1 to 2 esophageal varices are noted and banded. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, retrospective and limited prospective data have demonstrated the safety and effectiveness of DOACs compared to VKAs and LMWH in this cohort of patients (53). For example, Naymagon et al conducted a study comparing the use of DOACs with LMWH and Warfarin for the treatment of non-cirrhotic acute PVT.…”
Section: Diagnosismentioning
confidence: 99%
“…However, retrospective and limited prospective data have demonstrated the safety and effectiveness of DOACs compared to VKAs and LMWH in this cohort of patients (53). For example, Naymagon et al conducted a study comparing the use of DOACs with LMWH and Warfarin for the treatment of non-cirrhotic acute PVT.…”
Section: Diagnosismentioning
confidence: 99%
“…The use of DOACs, specific inhibitors of factor Xa or factor IIa, for the treatment of SVT remains contentious [87]. This is due to the registration trials for DOACs only including patients with PE or DVT: the studies do not include patients with any type of SVT, despite their advantages over anti-vitamin Kappa anticoagulants (VKAs) being relevant for patients with unusual site VTE [88][89][90].…”
Section: A Role For Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%
“…The 2020 ISTH guidelines suggested the possibility of using DOACs in patients without cirrhosis, with acute symptomatic SVT [85]. Retrospective studies and limited prospective data have demonstrated the safety and effectiveness of DOACs compared to VKAs and low molecular weight heparin (LMWH) in this cohort of patients [28,87,91,92]. In a retrospective trial, Naymagon et al compared the use of DOAC (Apixaban, Rivaroxaban and Dabigatran) with LMWH and Warfarin for the treatment of portal vein thrombosis in patients without cirrhosis.…”
Section: A Role For Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%